Analisis Perbedaan Antara Pengalaman Pembelian Online Dan Offline Dalam Mempengaruhi Prilaku Konsumen - Ana Sapitri; Anis Satun Nur Khoiriyah; Sintiawati Sintiawati; Riki Gana Suyatna (Pusat Riset dan Inovasi Nasional, 2024)
In this research, the focus is on the analysis to distinguish the influence of consumer behavior on online purchases and offline purchases. It is known that currently there are many sites to conduct online transactions and allow consumers to rely on online purchases to meet their needs. The experience in online purchasing tends to have a greater impact on consumer purchasing decisions compared to offline purchasing experiences. The method used in this research is a quantitative research method by conducting a questionnaire to a large number of respondents with certain categories aimed at collecting consumer shopping data. This data can then be analyzed using statistical methods to determine whether there is a significant difference between online purchases and offline purchases.